Cryo-electron microscopic structure of SecA protein bound to the 70S ribosome - Singh, Rajkumar (2018)
SecA is an ATP-dependent molecular motor pumping secretory and outer membrane proteins across the cytoplasmic membrane in bacteria. SecA associates with the protein-conducting channel, the heterotrimeric SecYEG complex, in a so-called posttranslational manner. A recent study further showed binding of a monomeric state of SecA to the ribosome. However, the true oligomeric state of SecA remains controversial because SecA can also form functional dimers, and high-resolution crystal structures exist for both the monomer and the dimer. Here we present the cryo-electron microscopy structures of Escherichia coli SecA bound to the ribosome. We show that not only a monomeric SecA binds to the ribosome but also that two copies of SecA can be observed that form an elongated dimer. Two copies of SecA completely surround the tunnel exit, providing a unique environment to the nascent polypeptides emerging from the ribosome. We identified the N-terminal helix of SecA required for a stable association with the ribosome. The structures indicate a possible function of the dimeric form of SecA at the ribosome.